Behavioral Phenotyping of Dopamine Transporter Knockout Rats: Compulsive Traits, Motor Stereotypies, and Anhedonia - Cinque, Stefano; Zoratto, Francesca; Poleggi, Anna; Leo, Damiana; Cerniglia, Luca; Cimino, Silvia; Tambelli, Renata; Alleva, Enrico; Gainetdinov, Raul R.; Laviola, Giovanni; Adriani, Walter (Frontiers in Psychiatry, 2018)
Alterations in dopamine neurotransmission are generally associated with diseases such as Attention-Deficit/Hyperactivity Disorder (ADHD) and Obsessive-Compulsive Disorder (OCD). Such diseases typically feature poor decision-making and lack of control on executive functions, and have been studied through the years using many animal models. Dopamine Transporter (DAT) knockout (KO) as well as heterozigous (HET) mice, in particular, have been widely used to study ADHD. Recently, a strain of DAT KO rats has been developed (Leo et al. 2018). Here, we provide a phenotypic characterization of reward sensitivity and compulsive choice by adult rats born from DAT-HET dams bred with DAT-HET males, in order to further validate DAT KO rats as an animal model for preclinical research. We first tested DAT KO rats’ sensitivity to rewarding stimuli, provided by highly appetitive food or sweet water; then, we tested their choice behavior with an Intolerance-to-Delay Task (IDT). During these tests, DAT KO rats appeared less sensitive to rewarding stimuli than WT and HET rats: they also showed a prominent hyperactive behavior with a rigid choice pattern, and a wide number of compulsive stereotypies. Moreover, during the IDT, we tested the effects of amphetamine and RO-5203648, a Trace Amine-Associated Receptor 1 (TAAR1) partial agonist. Amphetamine accentuated impulsive behaviors in WT and HET rats, while it had no effect in DAT KO rats. Finally, we measured the levels of Tyrosine Hydroxylase (TH), Dopamine Receptor 2 (D2), Serotonin Transporter (SERT) and TAAR1 mRNA transcripts in samples of ventral striatum, finding no significant differences between WT and KO genotypes. Throughout this study, DAT KO rats showed alterations in decision-making processes and in motivational states, as well as prominent motor stereotypies: more studies are warranted to fully characterize and efficiently use them in preclinical research.